Co-application of silicon and biochar affected anatomical and biochemical properties of corn leaf (Zea mays L.) under soil nickel toxicity - Ehsan Bijanzadeh; Hamid Reza Boostani; Ailsa G. Hardie; Mahdi Najafi-Ghiri (Heliyon)
Soil pollution with heavy metals is a threat to crop production. Practically, application of silicon (Si) with biochar can be a cost-effective approach to immobilize metals in contaminated soils. Investigation of the anatomical and biochemical changes of corn leaf is important for describing the mechanisms of Si and biochar soil application in alleviating the negative effects of nickel (Ni) toxicity. A factorial pot experiment was conducted to investigate the effect of Si (0, 250 and 500 mg Si kg−1 soil) in combination with rice husk biochar (RHB) or sheep manure biochar (SMB) prepared at two pyrolysis temperatures (300 and 500 °C) on anatomical and biochemical properties of corn leaves in a Ni-polluted soil. The length, width, area and weight of third-leaf, and metaxylem and protoxylem of midrib improved by application of Si250 with RHB more than SMB. At Si250, RHB300 and RHB500 improved the stomatal area by 31.7 and 27.7 % compared to control (without biochar), respectively. The leaf membrane stability index was increased by increasing Si application level and reached 69 % in RHB300. In contrast to total chlorophyll, the highest carotenoid content, catalase and peroxidase was obtained by control (without Si and biochar) followed by SMB. At Si250, the highest relative water content (RWC) was observed in RHB300 by 34.8 % increase. Also, RHB300 had the highest total dry matter, with increases of 82.2, 120.0 and 83.1 % at Si0, Si250 and Si500, respectively. By increasing the Si level and biochar application, the shoot Ni decreased between 42.1 and 133.3 %. Combined application of Si250 with RHB300 resulted in the highest dry matter through improving the leaf dimensions, metaxylem and protoxylem areas of midrib, membrane stability index, total chlorophyll, and RWC, while Ni uptake was reduced.